Reconstructing the morphologies and hydrodynamics of ancient rivers from source to sink: Cretaceous Western Interior Basin, Utah, USA - Lyster,SJ; Whittaker,AC; Hampson,GJ; Hajek,EA; Allison,PA; Lathrop,BA (Sedimentology, 2021)
Quantitative reconstruction of palaeohydrology from fluvial stratigraphy provides sophisticated insights into the response, and relative impact, of tectonic and climatic drivers on ancient fluvial landscapes. Here, field measurements and a suite of quantitative approaches are used to develop a four-dimensional (space and time) reconstruction of palaeohydrology in Late Cretaceous palaeorivers of central Utah, USA – these rivers drained the Sevier mountains to the Western Interior Seaway. Field data include grain-size and cross-set measurements and span five parallel fluvial systems, two of which include up-dip to down-dip transects, across seven stratigraphic intervals through the Blackhawk Formation, Castlegate Sandstone and Price River Formation. Reconstructed palaeohydrological parameters include fluvial morphologies (flow depths, palaeoslopes, palaeorelief and planform morphologies) and various hydrodynamic properties (flow velocities, water discharges and sediment transport modes). Results suggest that fluvial morphologies were similar in space and time; median flow depths spanned 2 to 4 m with marginally greater flow depths in southerly systems. Meanwhile palaeoslopes spanned 10−3 to 10−4, decreasing downstream by an order of magnitude. The most prominent spatio-temporal change is an up to four-fold increase in palaeoslope at the Blackhawk–Castlegate transition; associated alluvial palaeorelief is tens of metres during Blackhawk deposition and >100 m during Castlegate Sandstone deposition. This study observed no change in unit water discharges at the Blackhawk–Castlegate transition, which argues against a climatically driven increase in palaeoslope and channel steepness. These findings instead point to a tectonically driven palaeoslope increase, although one limitation in this study is uncertainty in palaeochannel widths, which directly influences total water discharges. These reconstructions complement and expand on extensive p